2011
DOI: 10.1097/olq.0b013e31820cb206
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Patients' Use of Expedited Partner Therapy

Abstract: Enhancing the counseling that accompanies EPT may improve patients' success in delivering it to their partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…7,12,13,1720 For PDPT, we used 5 estimates from 5 studies published between 2005 and 2011, using the same literature search (by keeping the patient referral and PDPT search time frames to the same period, we minimized time confounds). 12,13,2022 There were 1781 patients and 3125 partners. For DIS referral, we used program data on gonorrhea PN collected from a convenience sample of STD programs between 2010 and 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,12,13,1720 For PDPT, we used 5 estimates from 5 studies published between 2005 and 2011, using the same literature search (by keeping the patient referral and PDPT search time frames to the same period, we minimized time confounds). 12,13,2022 There were 1781 patients and 3125 partners. For DIS referral, we used program data on gonorrhea PN collected from a convenience sample of STD programs between 2010 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…One study in our sample, however, reported a high concordance between patient and partner reports of treatment ( r = 0.88), 20 and the estimates from another study with extensive patient follow-up questioning, including for adverse events such as domestic violence, were similar to those from studies with less intensive study. 22 Most data were collected in STD clinics or similar facilities; a broader variety of clinical settings would improve estimates for patient referral and PDPT. We also lacked sufficient studies and program estimates to generate distributions of estimates and thus propagate probabilities across the cascades.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Especially motivational interviewing helps patients to formulate their own needs and possible solutions. There is room for improvement with regard to counselling competencies of GPs [ 21 ]. A difference between professionals at GP practices and SHC is that the latter are used to address sexual health in a neutral way and use motivational interviewing [ 22 24 ], while some GPs seem to show uneasiness in discussing sexual health and use authoritative and judging manners in communication with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, most pharmacists agreed that the private consultation rooms in their pharmacy provided adequate privacy for an EPT consultation. It is well-documented that privacy and confidentiality are essential components of any form of partner treatment model [ 21 , 36 , 37 , 38 ]. Post-implementation research into pharmacist-provided EHC in Australia has shown that privacy is not always assured during sexual health consultations.…”
Section: Discussionmentioning
confidence: 99%